Design for reliability information and computer-based systems - Bauer, Eric (Hoboken, N.J. Wiley-IEEE Press, 2010)
"System reliability, availability and robustness are often not well understood by system architects, engineers and developers. They often don't understand what drives customer's availability expectations, how to frame verifiable availability/robustness requirements, how to manage and budget availability/robustness, how to methodically architect and design systems that meet robustness requirements, and so on. The book takes a very pragmatic approach of framing reliability and robustness as a functional aspect of a system so that architects, designers, developers and testers can address it as a concrete, functional attribute of a system, rather than an abstract, non-functional notion"--Provided by publisher.
Keywords: Reliability (Engineering).